Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Toko Kopi Tuku Bekasi Utara - Aditya Ahmad Maulana; Hadita Hadita (Universitas 45 Surabaya, 2024)
This journal aims to investigate how service quality and product quality at the Tuku Coffee Shop, North Bekasi, influence customer satisfaction. With a friendly approach, we explore the extent to which service and product quality contribute to positive customer experiences, and how this can increase the level of customer satisfaction. With a focus on warm interactions and the enjoyment of coffee, this research is expected to provide insight into the factors that form a positive relationship between customers and the Tuku Coffee Shop in North Bekasi. Since the emergence of the coffee industry in Indonesia, the Tuku Coffee Shop in North Bekasi has become as an inevitable destination for coffee lovers who appreciate authentic taste and a warm atmosphere. The customer experience at the Tuku Coffee Shop in North Bekasi does not just involve drinking a cup of coffee, it actually involves elements that create unforgettable memories. Customer satisfaction is not only a measure of service quality, but also the main pillar that influences the continuity and growth of a business.